Effect Comparison of Some Filters on Images - Arhoma, Amal Abdaslam; Badish, Nadia Ali; Aborawi, Hager Mohamed (المجلة العلمية لكلية التربية, 2023)
The study aims to enhance the processing of distorted digital images by applying filters like Low pass filter, High pass filter, Median filter, Mean filter, Max filter, Min filter, and High-boost filter. These filters depend on the modalities of the spatial and frequency domains, which use the method of blocking an image by window N * N. The study has been applied to binary image, grayscale image, and color image. With using kinds of noise such as salt and pepper noise, Gaussian noise, Speckle noise, and Poisson (Shot) noise. Processing was applied to a set of images to ensure the efficiency of the filters. In our work, a comparison was made between the results of these filters effect on the image